Ultrafast mapping in space and time of anisotropic light transport in nanowire mats - Luke Burke; Idris A. Ajia; Erik P. A. M. Bakkers; Otto L. Muskens (APL Photonics, 2025)
The study of interactions of light with highly scattering materials is important for applications in structural color, light trapping and localization, random lasing, and solar cells. Transport in such materials is governed by multiple scattering, and access to transport parameters, such as the mean free path and diffusion constant of light, is of interest to improve understanding and modeling of light in nanostructured materials. Here, we present results on ultrafast mapping of the time of flight of light inside dense mats of extremely scattering nanowires. We show that pump–probe transient absorption experiments allow for direct measurement of the transmission of light over a small area on the exit surface of the scattering material. Combined with static transport measurements, the process allows the determination of the diffusion constant independently in the transverse and longitudinal directions allowing to resolve anisotropic light transport in nanowire mats that are up to 30 μm thickness. The measured values for the diffusion constants and the energy transport velocities agree with previous measurements based on frequency speckle correlations.